Jalawastu Islamic People: The Struggle to Find Meaning in the "Ngasa Ritual" District Muslim Community Brebes - Dausat, Akrom Jangka; Nurhadi, Agus; Thohir, Mudjahirin; Listiana, Anisa (FIKRAH, 2024)
This article explains the controversial Ngasa ritual. The Ngasa ritual was originally an expression of gratitude to Batara Windu Buana, who is believed to be the creator of the universe who has provided abundant sustenance, so this ritual became controversial. This article aims to map the Jalawastu community and reveal the meaning behind the symbols of their life. Emic perception is the basis for exploring data and analyzing it using a semiotic paradigm. This researcher uses an ideational ethnographic approach. With this approach, it is hoped that many facts can be presented satisfactorily. The findings of this research indicate that there is a pattern of religious and cultural relations, namely the accumulative Islamic style adopted by the Jalawastu people in the Ngasanya tradition. The Jalawastu people, through the Ngasa ritual, formulate religious traditions between Islam according to their views and local traditions. On Tuesday Kliwon Mangsa Kasanga, they were completely.